A Comparative AHP Framework for Enhancing Urban Carbon Reduction Strategies in the Residential and Waste Management Sectors - Hidayat, Taufiq; Santoso, Imam; Koentjoro, Maharani Pertiwi (Department of Social Economy, Faculty of Agriculture , University of Brawijaya, 2026)
Purpose: Although residential and waste sector greenhouse gases from urban areas pose urgent challenges for medium-sized cities in developing countries, the latest mitigation studies tend to concentrate on metropolitan areas and sectors. Design/Methodology/Approach: This paper presents a new comparative Analytic Hierarchy Process (AHP) framework in which cross-sectoral residential and waste strategies come together on the basis of a multistakeholder decision-making model for medium-sized cities in developing countries. Utilizing Mojokerto City, Indonesia as a case study, five criteria emission reduction effectiveness, implementation cost, ease of implementation, public acceptance, and policy support were evaluated for seven mitigation options. We chose 10 purposively selected experts from academics, practitioners, policymakers, non-governmental organizations, and community groups to provide sources of data. Findings: The results show the separation of organic and inorganic waste, as well as processing organic waste, are the most important strategies due to their prominent mitigation effect, behavioral feasibility, and social acceptability. Technological-based and compliance-oriented initiatives ranked among the moderate to lower-ranking measures, as institutional and practical constraints dictate. Originality/Value/Novelty: This study is novel in its interdependency on comparative weighting among multistakeholder analyses which identifies trade-offs, preference divergences, and consensus patterns between actor groups, contributing to an adaptive and replicable priority-setting model for medium-sized cities aiming for inclusive, context-sensitive low-carbon transitions.